Green Process: Improved Semi-Continuous Fermentation of Pichia pastoris Based on the Principle of Vitality Cell Separation - Denggang Wang; Wenjie Li; Xinying Zhang; Shuli Liang; Ying Lin (Frontiers in Bioengineering and Biotechnology, 2021)
The large-scale fermentation of Pichia pastoris for recombinant protein production would be time consuming and produce a large amount of waste yeast. Here we introduce a novel semi-continuous fermentation process for P. pastoris GS115 that can separate vitality cells from broth and recycle the cells to produce high-secretory recombinant pectate lyase. It is based on differences in cell sedimentation coefficients with the formation of salt bridges between metal ions and various cell states. Compared to batch-fed cultivation and general semi-continuous culture, the novel process has significant advantages, such as consuming fewer resources, taking less time, and producing less waste yeast. Sedimentation with the addition of Fe3+ metal ions consumed 14.8 ± 0.0% glycerol, 97.8 ± 1.3% methanol, 55.0 ± 0.9 inorganic salts, 81.5 ± 0.0% time cost, and 77.0 ± 0.1% waste yeast versus batch-fed cultivation to produce an equal amount of protein; in addition, the cost of solid–liquid separation was lower for cells in the collected fermentation broth. The process is economically and environmentally efficient for producing recombinant proteins.